Aberrant DNA methylation of alternative promoter of DLC1 isoform 1 in meningiomas - Bujko, M. (J Neurooncol, 2016)
DLC1 encodes GTPase-activating protein with a well-documented tumor suppressor activity. This gene is downregulated in various tumors through aberrant promoter hypermethylation. Five different DLC1 isoforms can be transcribed from alternative promoters. Tumor-related DNA methylation of the DLC1 isoform 1 alternative promoter was identified as being hypermethylated in meningiomas in genome-wide DNA methylation profiling. We determined the methylation pattern of this region in 50 meningioma FFPE samples and sections of 6 normal meninges, with targeted bisulfite sequencing. All histopathological subtypes of meningiomas showed similar and significant increase of DNA methylation levels. High DNA methylation was associated with lack of DLC1 protein expression in meningiomas as determined by immunohistochemistry. mRNA expression levels of 5 isoforms of DLC1 transcript were measured in an additional series of meningiomas and normal meninges. The DLC1 isoform 1 was found as the most expressed in normal control tissue and was significantly downregulated in meningiomas. Transfection of KT21 meningioma cell line with shRNA targeting DLC1 isoform 1 resulted in increased activation of RHO-GTPases assessed with pull-down assay, enhanced cell migration observed in scratch assay as well as slight increase of cell metabolism determind by MTT test. Results indicate that isoform 1 represents the main pool of DLC1 protein in meninges and its downregulation in meningiomas is associated with hypermethylation of CpG dinucleotides within the corresponding promoter region. This isoform is functional GAP protein and tumor suppressor and targeting of its expression results in the increase of DLC1 related cell processes: RHO activation and cell migration.